Optimization of Poultry Physiological Condition in the Post-Antibiotic Era through Nutritional Intervention – A Review - Sugiharto, Sugiharto; Raza, Muhammad Asif (Jurnal Medik Veteriner, 2024)
The intestinal microbe population has a considerable impact on the physiological state of poultry. Nutritional intervention can be used to enhance the equilibrium of the gut microbiota in chickens, leading to good physiological effects. Various nutritional interventions have been implemented, including feed additives, vitamins, and fermented and functional feeds. While numerous studies have shown the efficacy of nutritional strategies, others have noted the variability of these interventions on poultry’s physiological state. Various factors can influence the effectiveness of nutritional interventions on the physiological conditions of poultry, such as the types of feed additives or active components, duration and method of administration, feed composition, environmental conditions during rearing, quality of day-old-chick, type and age of poultry, hygiene, infection, stress, and other related variables. Feed additives, when combined with nutritional components or other active chemicals, can have synergistic and complementary effects. These impacts could improve the effectiveness and reliability of the nutritional interventions on physiological parameters and poultry productivity. Furthermore, combinations can include feed additives or active components like probiotics and acidifiers, probiotics and enzymes, phytobiotics and enzymes, and plant-based materials and chitosan. The combinations show synergistic and complementary benefits, improving physiological conditions in chickens more than using feed additives or active substances alone. Overall, nutritional intervention can be used to improve the microbial balance in poultry intestines and boost their physiological state. Moreover, integrating feed additives with other active components might enhance the physiological circumstances of chickens due to the synergistic effect produced by their combination.